Economic Empowerment Through Entrepreneurship Training to Advance Youth in Quetta, Pakistan - Khurshed Iqbal; Tamrin Fathoni; Lisma Meilia Wijayanti; Medina Nur Asyifah Purnama (Edujavare Publishing, 2023)
The purpose of writing this work is to understand the concept of assisting economic empowerment through entrepreneurship training to advance youth in Quetta, Pakistan. Economic empowerment through entrepreneurship training in Quetta, Pakistan, adopts a robust and holistic mentoring method known as the ABCD (Asset-Based Community Development). The result of this work is that ten key components have been identified in efforts to empower youth in Quetta, Pakistan. Mentorship and business consultation offer invaluable guidance and support for business development. Access to capital facilitates efficient business initiation and growth, while advanced training enhances specialized skills. Networking and business connections are essential for youth advancement, and psychological guidance helps them cope with stress. Effective online and offline marketing and promotion ensure successful product and service promotion. Access to resources, including co-working spaces and software, reduces barriers to entry and improves efficiency. Finally, financial education equips youth with wise financial management skills. With these components, Quetta's youth have a greater opportunity to achieve economic success and contribute to their community's economic development. The research findings highlight that a comprehensive economic empowerment program in Quetta, Pakistan, incorporating mentorship, business consulting, access to capital, advanced training, networking, psychological support, effective marketing, resource access, and financial education, significantly enhances the potential for youth economic success and contributes to community development. Collectively, these key components create a supportive ecosystem for young entrepreneurs in Quetta to thrive in their businesses.